Preparation method of perovskite nanocrystals, radiation-resistant perovskite vulcanized silicone rubber and preparation method of radiation-resistant perovskite vulcanized silicone rubber
By using perovskite nanocrystals as radiation-resistant additives in silicon rubber and cross-linking reactions through limited component ratios, the problem of aging of silicon rubber in high-energy ray environment is solved, and the excellent radiation-resistant of silicon rubber is achieved and heat-resistant aging properties.
Patent Information
- Application Number
- CN202411716736.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-25
AI Technical Summary
The existing silicone rubber materials age in high-energy ray environments and reduce mechanical properties, which threatens the safety and stability of the equipment.
Perovskite nanocrystals are used as radiation-resistant additives, and radiation-resistant perovskite vulcanized silicone rubber is prepared by limiting the proportion of each component. The method includes dissolving AX and BX2 in a solvent, adding ligands for ultrasonic treatment, forming a precursor solution, and then precipitating perovskite nanocrystals in a stirring reaction, and cross-linking reaction with a silicone rubber-based glue.
The obtained silicone rubber has excellent radiation resistance and heat-aging resistance, excellent mechanical properties, wide application range, and simpler and more efficient preparation process.
Smart Images

Figure CN119503865A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a method for preparing perovskite nanocrystals, radiation-resistant perovskite vulcanized silicone rubber and a preparation method thereof, and belongs to the technical field of organic silicon materials. Background Art
[0002] With the continuous development of aerospace, medical and health, and nuclear industry technologies, the safety factor requirements for equipment are becoming higher and higher. In order to better ensure safety, a large number of polymer elastomers are used as sealing materials in temperature control coating adhesives for spacecraft surface materials and in atomic energy equipment such as wires and cables, electrical instruments, etc. in nuclear power and nuclear energy industries. However, this type of sealing rubber material will experience severe aging and severe degradation of mechanical properties in the environment of high-energy rays, causing immeasurable losses to people's lives and financial security. Therefore, the preparation of silicone rubber sealing materials with excellent radiation resistance is the key to improving equipment safety and stability.
[0003] In order to improve the radiation resistance of silicone rubber, it is a common approach to use methylphenyl silicone rubber instead of traditional dimethyl silicone rubber and to use rare earth oxides as radiation-resistant additives. However, the process of phenyl-containing silicone rubber is difficult and difficult to vulcanize, and its resilience and mechanical strength are not ideal. Chinese patent CN101775219B discloses a radiation-resistant addition-type room temperature vulcanized liquid silicone rubber and its preparation method, and records that rare earth oxides can be used to improve the radiation resistance of silicone rubber. However, rare earth oxides have poor compatibility with silicone rubber, and more complex reaction conditions are required to improve the radiation resistance of silicone rubber. Summary of the invention
[0004] In order to solve the above problems, the present application proposes a method for preparing perovskite nanocrystals, radiation-resistant perovskite vulcanized silicone rubber and a preparation method thereof. By using perovskite nanocrystals as radiation-resistant additives and limiting the proportion of each component, the obtained silicone rubber has excellent radiation resistance, heat resistance and anti-aging properties, excellent mechanical properties, and wide application; at the same time, the preparation process of radiation-resistant perovskite room temperature vulcanized rubber is simpler and more efficient.
[0005] According to one aspect of the present application, a method for preparing perovskite nanocrystals is provided, comprising the following steps:
[0006] (1) AX and BX 2 Add the mixture into a solvent and fully dissolve it to obtain a mixed solution;
[0007] (2) adding a ligand to the mixed solution, and sonicating until fully dissolved to obtain a uniform precursor solution, wherein the ligand is a Lewis acid and an aminosilane;
[0008] (3) adding the precursor solution into the solvent and stirring to react;
[0009] (4) The product obtained in step (3) is centrifuged to obtain a precipitate of ABX 3 Perovskite nanocrystals, the ABX 3 Perovskite nanocrystals are lead halide perovskite nanocrystals, where A is Cs + , CH 3 NH 3 + , NH 2 -CH=NH 2 + At least one of the following, B is Pb 2+ , X is Cl - ,Br - , I - At least one of .
[0010] Specifically, the solvent in step (1) can convert AX, BX 2 It can be dissolved, preferably at least one of N, N-dimethylformamide and dimethyl sulfoxide;
[0011] Step (2) uses Lewis acid and aminosilane as ligands to improve the stability of perovskite nanocrystals;
[0012] The solvent in step (3) is a solvent with low polarity that can cause the precursor solution to precipitate crystals, specifically including one or more of acetone, butanone, cyclohexanone, toluene, dichloromethane, chloroform, n-hexane, and ethyl acetate.
[0013] Specifically, AX is one or more of cesium chloride, cesium bromide, cesium iodide, methylammonium chloride, methylammonium bromide, methylammonium iodide, formamidine hydrochloride, formamidine hydrobromide, and formamidine hydroiodide, and BX 2 It is one or more of lead chloride, lead bromide and lead iodide.
[0014] Specifically, the ABX 3 Perovskite nanocrystals are CsPbBr 3 、CsPbCl 3 , CsPbI 3 , CsPbBr X I 3-X (0≤x≤3), CsPbBr X Cl 3-X (0≤x≤3), CH 3 NH 3 PbI 3 、CH(NH 2 ) 2 PbI 3 , CH 3 NH 3 PbBX I 3-X One or more of (0≤x≤3).
[0015] Optionally, in step (1), AX and BX 2 The molar ratio is 1:1.
[0016] Optionally, the Lewis acid in step (2) is one of poly(maleic anhydride-alt-1-octadecene), oleic acid or octylphosphonic acid, preferably poly(maleic anhydride-alt-1-octadecene).
[0017] Specifically, poly(maleic anhydride-alt-1-octadecene) is a polymer multidentate ligand with multiple anhydrides at one end that can simultaneously coordinate with the surface of perovskite nanocrystals, playing a good stabilizing role and passivating defect effects; the long octadecene carbon chain at the other end acts as a hydrophobic carbon chain that can effectively prevent the damage of moisture in the environment to the perovskite nanocrystals; at the same time, poly(maleic anhydride-alt-1-octadecene) can also enhance the effective adhesion of aminopropyltriethoxysilane on the surface of perovskite nanocrystals, playing a good synergistic effect.
[0018] Alternatively, aminosilicone refers to a polysiloxane having -NH 2 Siloxane compounds with amino groups can repair halogen vacancies to improve the photostability of perovskite nanocrystals;
[0019] The aminosiloxane is selected from aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, and N-aminoethyl-3-aminopropyltriethoxysilane, and is preferably aminopropyltriethoxysilane; the aminosiloxane can make the surface of the perovskite nanocrystal have a large number of siloxy groups, giving the perovskite nanocrystal functionality, and the perovskite nanocrystal is used in silicone rubber, and the siloxy groups on the surface are hydrolyzed and condensed with the cross-linked network of the silicone rubber to form a three-dimensional cross-linked network, thereby improving the compatibility of the perovskite nanocrystal with the silicone rubber, increasing the dispersibility of the perovskite nanocrystal, making the overall performance of the material more uniform and improving the overall radiation resistance and heat aging resistance of the material.
[0020] Optionally, the mass ratio of the Lewis acid to the aminosilicone is 1:(1-20).
[0021] Specifically, if the amount of aminosiloxane is too little, the compatibility of the obtained nanocrystals with silicone rubber will be poor, while if the amount of aminosiloxane is too much, the crystal structure of the perovskite will be destroyed, affecting the radiation resistance of the silicone rubber.
[0022] The AX and BX 2 The mass ratio of the total amount to the total amount of ligands is 1:(1-20), preferably 1:(8-14);
[0023] Specifically, if the amount of ligand is too small, the defects on the surface of the perovskite cannot be passivated well and it is more easily deliquesced in the air, so the stability will be poor, and the compatibility with silicone rubber will also deteriorate; if the amount of ligand is too large, a thicker organic layer will be formed, resulting in uneven particle size of the nanocrystals, affecting the radiation resistance.
[0024] Optionally, the ultrasonic treatment time in step (2) is 2-20 minutes.
[0025] Optionally, the stirring process in step (3) is carried out at a rotation speed of 300-1000 rpm for 5-15 minutes.
[0026] The stirring process of step (3) is rapid stirring. After the precursor solution is added to the solvent, crystals will immediately precipitate to obtain perovskite nanocrystals. Rapid stirring helps to obtain perovskite nanocrystals with more uniform particle sizes and reduces the probability of agglomeration of perovskite nanocrystals.
[0027] If the reaction time is too short, the number of silicon ethoxy groups on the surface of the perovskite nanocrystals will be small, reducing the compatibility with silicone rubber; if the reaction time is too long, the perovskite nanocrystals will grow too large and the particle size will be relatively uneven.
[0028] Optionally, the centrifugation process in step (4) is performed by centrifuging in a high-speed centrifuge at a speed of 500-15000 rpm for 2-30 minutes.
[0029] According to another aspect of the present application, a radiation-resistant perovskite vulcanized silicone rubber is provided, which is prepared from the following components:
[0030] 100 parts of base rubber, 2-60 parts of radiation-resistant additive, 10-60 parts of reinforcing filler, 1-10 parts of cross-linking agent, 0.2-5 parts of catalyst;
[0031] The radiation-resistant additive is ABX prepared by the aforementioned method. 3 Perovskite nanocrystals.
[0032] Optionally, the cross-linking agent is a silane coupling agent containing at least three siloxy groups;
[0033] Specifically, the crosslinking agent is at least one of tetraethyl silicate, polyethyl silicate or methyltriethoxysilane, preferably tetraethyl silicate.
[0034] The siloxy groups of the crosslinking agent and the siloxy groups on the surface of the perovskite nanocrystals react with the hydroxyl groups in the base rubber under the action of a catalyst to form siloxy bonds (Si-O-Si) and remove ethanol. As the reaction proceeds, a crosslinking network is formed, thereby curing the system to obtain silicone rubber.
[0035] Optionally, the reinforcing filler is at least one of white carbon black, carbon black and calcium carbonate. Preferably, the reinforcing filler is white carbon black, and the average particle size of the white carbon black is 10-30 nanometers, and the specific surface area is 70-320 m 2 / g,SiO 2 The content is not less than 99.8%.
[0036] Specifically, the reinforcing filler silica is preferably fumed silica. If too much silica is used, the hardness of the silicone rubber will increase and the elasticity will deteriorate. If too little is used, the mechanical strength will be too low and the ideal reinforcement effect cannot be achieved. Too much cross-linking agent will cause the silicone rubber to become brittle and hard, and the elasticity will decrease. If too little is used, the mechanical properties of the rubber will be poor. If too much catalyst is used, the vulcanization rate will be too fast and it will affect the aging resistance of the silicone rubber. If too little is used, the rubber cannot be vulcanized.
[0037] If the amount of radiation-resistant additive is too little, the radiation resistance and heat aging resistance of silicone rubber will not be improved well. If the amount of radiation-resistant additive is too much, the radiation-resistant additive will agglomerate in the silicone rubber and reduce the dispersibility of white carbon black, thus affecting the mechanical properties of silicone rubber. In addition, since the radiation-resistant additive contains silicon ethoxy groups on its surface, it can also improve the dispersibility of white carbon black in the base rubber, so that the radiation-resistant additive and white carbon black are evenly dispersed in the base rubber, and silicone rubber with better performance is obtained under the cross-linking action of the cross-linking agent.
[0038] Optionally, the base glue is a hydroxyl-terminated polysiloxane with a molecular weight of 5000-30000.
[0039] Specifically, the base glue is one of α,ω-dihydroxy polydimethylsiloxane, α,ω-dihydroxy poly (dimethyl, diphenyl) siloxane, α,ω-dihydroxy poly (dimethyl, methylphenyl) siloxane, and α,ω-dihydroxy polymethyl trifluoropropyl siloxane. The base glue contains dihydroxyl groups, which can react with a crosslinking agent under the action of a catalyst, and hydrolyze and condense after dealcoholization to form a crosslinking network.
[0040] Optionally, the catalyst is at least one of dibutyltin dilaurate or stannous octoate, preferably dibutyltin dilaurate; the catalyst is used to catalyze the condensation cross-linking reaction between the hydroxyl groups in the base rubber and the cross-linking agent, remove the small molecule ethanol, and form a dealcoholized room temperature vulcanized silicone rubber.
[0041] According to another aspect of the present application, there is provided a method for preparing the silicone rubber as described above, comprising the following steps:
[0042] (1) fully mixing the base rubber, the anti-radiation additive, and the reinforcing filler, and the mixing process is carried out in a three-dimensional mixer;
[0043] (2) adding a crosslinking agent and a catalyst to the mixture of step (1), and mixing them uniformly to obtain a silicone rubber base material;
[0044] (3) The silicone rubber base material is poured into a polytetrafluoroethylene mold for vulcanization to obtain radiation-resistant perovskite vulcanized silicone rubber.
[0045] The beneficial effects of this application include but are not limited to:
[0046] 1. The radiation-resistant perovskite vulcanized silicone rubber provided in the present application uses perovskite nanocrystals as the radiation-resistant additive of the vulcanized silicone rubber, has a good absorption effect on high-energy rays, and then converts them into visible light for emission, so that the silicone rubber has excellent radiation resistance and heat aging resistance; the use of perovskite nanocrystals as the radiation-resistant additive of the vulcanized silicone rubber also makes the preparation process of the vulcanized silicone rubber simpler and more efficient.
[0047] 2. The radiation-resistant perovskite vulcanized silicone rubber provided in the present application adopts aminopropyltriethoxysilane as a ligand to prepare perovskite nanocrystals. The obtained perovskite nanocrystals have a large number of silylethoxy groups on their surfaces. After being mixed into the silicone rubber base, under the action of a catalyst, the silylethoxy groups on the surface of the perovskite react with the silyloxy groups of the cross-linking agent and the hydroxyl groups in the base to form silicon-oxygen bonds (Si-O-Si), and ethanol is removed. As the reaction proceeds, a cross-linked network is formed, thereby curing the system and making the perovskite nanocrystals more compatible with the silicone rubber, so that the prepared vulcanized silicone rubber is more uniform, thereby improving the overall radiation resistance and heat aging resistance of the material.
[0048] 3. The radiation-resistant perovskite sulfide silicone rubber provided in the present application is obtained by limiting the halide AX and BX 2 The ratio between the nanocrystals and the ligands allows the obtained perovskite nanocrystals to maintain good stability and at the same time improves the compatibility of the nanocrystals with silicone rubber. The nanocrystals are more evenly distributed in the silicone rubber, making the radiation resistance of the silicone rubber better.
[0049] 4. The radiation-resistant perovskite vulcanized silicone rubber provided in the present application improves the change in tensile strength, elongation at break and hardness of the vulcanized silicone rubber before and after irradiation by limiting the ratio of white carbon black to the cross-linking agent in the material components, so that the radiation resistance and anti-aging performance of the obtained vulcanized silicone rubber material are more excellent. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0051] Figure 1This is the XRD diffraction pattern of the perovskite nanocrystals prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0052] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0053] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention. The preferred implementation methods and materials described in this patent are for demonstration purposes only.
[0054] The molecular weight of the poly(maleic anhydride-alt-1-octadecene) used in the following examples is 1370-3650, and the average molecular weight is 1980.
[0055] Example 1
[0056] The method for preparing perovskite nanocrystals comprises the following steps:
[0057] (1) AX and BX 2 Add into solvent A and fully dissolve to obtain a mixed solution;
[0058] (2) adding the ligand to the mixed solution and sonicating until it is fully dissolved to obtain a uniform precursor solution;
[0059] (3) Add the precursor solution into solvent B and stir to react;
[0060] (4) The product obtained in step (3) is centrifuged to obtain a precipitate of ABX 3 Perovskite nanocrystals.
[0061] According to the above preparation method, the following perovskite nanocrystals 1#-10# and D1#-D8# are prepared, as follows:
[0062] Perovskite Nanocrystal 1#
[0063] (1) Weigh 0.4 mmol of CsBr and 0.4 mmol of PbBr 2 Place in a beaker and measure 10 mL of N,N-dimethylformamide (DMF) into the beaker to completely dissolve the solute;
[0064] (2) Weigh 0.2 g of poly(maleic anhydride-alt-1-octadecene) and 2 g of aminopropyltriethoxysilane into the beaker of step (1), and perform ultrasonication for 10 minutes to fully mix and dissolve them to obtain a uniform precursor solution;
[0065] (3) 1 mL of the precursor solution was added to a toluene solution stirred at 600 rpm and stirred for 10 min to obtain a bright green solution;
[0066] (4) The product obtained in step (3) was centrifuged at 10,000 rpm for 10 minutes in a high-speed centrifuge, the supernatant was discarded, and the precipitate was collected to obtain CsPbBr 3 Perovskite nanocrystals.
[0067] XRD characterization of perovskite nanocrystal 1# is performed, and the characterization results are shown in Figure 1 .
[0068] From the XRD spectrum, it can be seen that the diffraction peaks of the perovskite nanocrystals can correspond well to the standard card, and no impurities appear, indicating that pure phase perovskite nanocrystals have been prepared.
[0069] Perovskite Nanocrystal 2#
[0070] (1) Weigh 0.4 mmol of CsBr and 0.4 mmol of PbBr 2 Place in a beaker and measure 10 mL of N,N-dimethylformamide (DMF) into the beaker to completely dissolve the solute;
[0071] (2) Weigh 0.2 g of poly(maleic anhydride-alt-1-octadecene) and 2 g of aminopropyltriethoxysilane into the beaker of step (1), and perform ultrasonication for 2 minutes to fully mix and dissolve them to obtain a uniform precursor solution;
[0072] (3) 1 mL of the precursor solution was added to a toluene solution stirred at 300 rpm and stirred for 15 min to obtain a bright green solution;
[0073] (4) The product obtained in step (3) was centrifuged at 500 rpm for 30 minutes in a high-speed centrifuge, the supernatant was discarded, and the precipitate was collected to obtain CsPbBr 3 Perovskite nanocrystals.
[0074] Perovskite Nanocrystal 3#
[0075] (1) Weigh 0.4 mmol of CsBr and 0.4 mmol of PbBr 2 Place in a beaker and measure 10 mL of N,N-dimethylformamide (DMF) into the beaker to completely dissolve the solute;
[0076] (2) Weigh 0.2 g of poly(maleic anhydride-alt-1-octadecene) and 2 g of aminopropyltriethoxysilane into the beaker of step (1), and perform ultrasonication for 20 minutes to fully mix and dissolve them to obtain a uniform precursor solution;
[0077] (3) 1 mL of the precursor solution was added to a toluene solution stirred at 1000 rpm and stirred for 5 minutes to obtain a bright green solution;
[0078] (4) The product obtained in step (3) was centrifuged at 15,000 rpm for 2 minutes in a high-speed centrifuge, the supernatant was discarded, and the precipitate was collected to obtain CsPbBr 3 Perovskite nanocrystals.
[0079] Perovskite Nanocrystal 4#
[0080] Compared with perovskite nanocrystal 1#, the difference is that AX, BX 2 CsCl, PbCl 2 , and the rest are the same as perovskite nanocrystal 1#.
[0081] Perovskite Nanocrystal 5#
[0082] Compared with perovskite nanocrystal 1#, the difference is that AX, BX 2 CsI, PbI 2 , and the rest are the same as perovskite nanocrystal 1#.
[0083] Perovskite Nanocrystal 6#
[0084] Compared with perovskite nanocrystal 1#, the difference is that AX is CH 3 NH 3 Br, and the ligands 0.2g poly(maleic anhydride-alt-1-octadecene) and 2g aminopropyltriethoxysilane were replaced by 0.6g poly(maleic anhydride-alt-1-octadecene) and 6g aminopropyltriethoxysilane, and the rest were the same as perovskite nanocrystal 1#.
[0085] Perovskite Nanocrystal 7#
[0086] Compared with perovskite nanocrystal 1#, the difference is that AX is CH(NH 2 ) 2 Br, the ligand 0.2g poly(maleic anhydride-alt-1-octadecene) and 2g aminopropyltriethoxysilane were replaced with 0.1g poly(maleic anhydride-alt-1-octadecene) and 2.5g aminopropyltriethoxysilane, and the rest was the same as perovskite nanocrystal 1#.
[0087] Perovskite Nanocrystal 8#
[0088] Compared with perovskite nanocrystal 1#, the difference is that the ligand 0.2g poly(maleic anhydride-alt-1-octadecene) and 2g aminopropyltriethoxysilane are replaced with 1.5g poly(maleic anhydride-alt-1-octadecene) and 0.7g aminopropyltriethoxysilane, and the rest is the same as perovskite nanocrystal 1#.
[0089] Perovskite Nanocrystal 9#
[0090] Compared with perovskite nanocrystal 1#, the difference is that the ligand aminopropyltriethoxysilane is replaced by 3-aminopropyltrimethoxysilane, and the rest is the same as perovskite nanocrystal 1#.
[0091] Perovskite Nanocrystal 10#
[0092] Compared with perovskite nanocrystal 1#, the difference is that the ligand poly(maleic anhydride-alt-1-octadecene) is replaced by oleic acid, and the rest is the same as perovskite nanocrystal 1#.
[0093] Perovskite Nanocrystal D1#
[0094] Compared with perovskite nanocrystal 1#, the difference is that it does not contain aminopropyltriethoxysilane ligand, only poly(maleic anhydride-alt-1-octadecene) ligand, and the rest is the same as perovskite nanocrystal 1#.
[0095] Perovskite Nanocrystal D2#
[0096] Compared with perovskite nanocrystal 1#, the difference is that it does not contain poly(maleic anhydride-alt-1-octadecene) ligand, only has aminopropyltriethoxysilane ligand, and the rest is the same as perovskite nanocrystal 1#.
[0097] Example 2
[0098] The preparation method of vulcanized silicone rubber 1# comprises the following steps:
[0099] (1) Add 100 parts of α,ω-dihydroxypolydimethylsiloxane (molecular weight 10,000), 10 parts of perovskite nanocrystal 1#, and 30 parts of fumed silica into a mixing box and mix them thoroughly in a three-dimensional mixer;
[0100] (2) Add 3 parts of ethyl orthosilicate and 1.5 parts of dibutyltin dilaurate into a mixing box and mix well again;
[0101] (3) Pour the mixed raw materials in step (2) into a polytetrafluoroethylene mold and vulcanize at room temperature to obtain vulcanized silicone rubber 1#.
[0102] The following vulcanized silicone rubbers 2#-11# and D1#-D7# were prepared in the same manner as the above-mentioned vulcanized silicone rubber 1#. The specific differences are shown in Table 1:
[0103] Table 1 Ratio of materials used for vulcanized silicone rubber (parts by weight)
[0104]
[0105]
[0106] The newly added 11# uses calcium carbonate as reinforcing filler, and the other components are the same as 1# vulcanized silicone rubber.
[0107] The vulcanization time of the above silicone rubber is roughly within 12h-72h, as long as the vulcanization of the silicone rubber can be completed.
[0108] Experimental example
[0109] The performance test of the radiation-resistant vulcanized silicone rubber product obtained in Example 2 above:
[0110] 1. Irradiation performance
[0111] The irradiation source is Co60-γ ray irradiation. The sample receives a total irradiation dose of 500 Kgy in air, and the irradiation dose rate is 30 Gy / min.
[0112] 2. Mechanical properties test
[0113] Tensile strength and elongation: tested according to GB / T528-1998; Hardness: tested according to GB / T531-1999.
[0114] The results are shown in Table 2.
[0115] Table 2 Radiation resistance properties of radiation-resistant vulcanized silicone rubber
[0116]
[0117]
[0118] From the above results, it can be seen that the silicone rubber obtained by the formula and preparation method specified in this application has smaller changes in tensile strength, elongation at break and hardness before and after irradiation, still has good mechanical properties after irradiation, and excellent radiation resistance.
[0119] Each embodiment in this specification is described in a progressive manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.
[0120] The above is only an embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included in the scope of the claims of the present application.
Claims
1. A method for preparing perovskite nanocrystals, characterized in that: The following steps are involved: (1) adding AX and BX2 into a solvent and fully dissolving them to obtain a mixed solution; (2) adding a ligand to the mixed solution, and sonicating until fully dissolved to obtain a uniform precursor solution, wherein the ligand is a Lewis acid and an aminosiloxane; (3) adding the precursor solution into the solvent and stirring to react; (4) centrifuging the product obtained in step (3), and the resulting precipitate is ABX3 perovskite nanocrystal, wherein the ABX3 perovskite nanocrystal is a lead halide perovskite nanocrystal, wherein A is Cs + , CH3NH3 + , NH2-CH=NH2 + At least one of the following, B is Pb 2+ , X is Cl - ,Br - , I - At least one of .
2. The method for preparing perovskite nanocrystals according to claim 1, characterized in that: The molar ratio of AX to BX2 in step (1) is 1:
1.
3. The method for preparing perovskite nanocrystals according to claim 1, characterized in that: The Lewis acid in step (2) is at least one of poly(maleic anhydride-alt-1-octadecene), oleic acid, and octylphosphonic acid.
4. The method for preparing perovskite nanocrystals according to claim 1, characterized in that: The aminosiloxane is selected from aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, and N-aminoethyl-3-aminopropyltriethoxysilane.
5. The method for preparing perovskite nanocrystals according to claim 1, characterized in that: The mass ratio of the Lewis acid to the aminosilane is 1:(1-20).
6. The method for preparing perovskite nanocrystals according to claim 1, characterized in that: The mass ratio of the total amount of AX and BX2 to the total amount of ligand is 1:(1-20).
7. A radiation-resistant perovskite vulcanized silicone rubber, characterized in that: According to parts by weight, it is prepared from the following components: 100 parts of base rubber, 2-60 parts of radiation-resistant additive, 10-60 parts of reinforcing filler, 1-10 parts of cross-linking agent, 0.2-5 parts of catalyst; The radiation-resistant additive is an ABX3 perovskite nanocrystal prepared by the method according to any one of claims 1 to 6.
8. The radiation-resistant perovskite vulcanized silicone rubber according to claim 7, characterized in that: The cross-linking agent is a silane coupling agent containing at least three siloxy groups.
9. The radiation-resistant perovskite vulcanized silicone rubber according to claim 7, characterized in that: The reinforcing filler is at least one of white carbon black, carbon black and calcium carbonate, preferably white carbon black; The base glue is hydroxyl-terminated polysiloxane with a molecular weight of 5000-30000.
10. A method for preparing the radiation-resistant perovskite vulcanized silicone rubber according to any one of claims 7 to 9, characterized in that: The following steps are involved: (1) Fully mix the base rubber, anti-radiation additives and reinforcing fillers; (2) adding a crosslinking agent and a catalyst to the mixture of step (1), and mixing them uniformly to obtain a silicone rubber base material; (3) The silicone rubber base material is poured into a mold and vulcanized to obtain radiation-resistant perovskite vulcanized silicone rubber.
Citation Information
Patent Citations
Radiation-resistant addition type room temperature vulcanized liquid silicone rubber and preparation method thereof
CN101775219B